Multimodality imaging for resuscitated sudden cardiac death. (January 2015) - Chen, Yingming Amy; Deva, Djeven; Kirpalani, Anish; Prabhudesai, Vikram; Marcuzzi, Danny W.; Graham, John J.; Verma, Subodh; Jimenez-Juan, Laura; Yan, Andrew T.
Abstract : We present a case that elegantly illustrates the utility of two novel noninvasive imaging techniques, computed tomography (CT) coronary angiography and cardiac MRI, in the diagnosis and management of a 27-year-old man with exertion-induced cardiac arrest caused by an anomalous right coronary artery. CT coronary angiography with 3D reformatting delineated the interarterial course of an anomalous right coronary artery compressed between the aorta and pulmonary artery, whereas cardiac MRI showed a small myocardial infarction in the right coronary artery territory not detected on echocardiography. This case highlights the value of novel multimodality imaging techniques in the risk stratification and management of patients with resuscitated cardiac arrest.